Effect of Hydrogel Epigallocatechin-3-Gallate (EGCG) to the Number of Fibroblast Cell Proliferation in the Perforation of Wistar Rat Tooth Pulp - Ira Widjiastuti; Setyabudi setyabudi; Kun Ismiyatin; Djoko Agus Purwanto; Tiara Sukmawati (Conservative Dentistry Journal, 2019)
Background: Pulpitis can occur because the deep cavity preparation and it causes increasing of NO levels. Perforated teeth require direct pulp capping (DPC) treatment. The current standard DPC material is calcium hydroxide. However, several studies have found weaknesses of calcium hydroxide that can affect the success of DPC treatment and new, more biocompatible materials are needed. Epigallocatechin-3-gallate (EGCG) in green tea has many benefits, including antioxidant, anticolagenase, anticancer, anti-inflammatory and has the ability of radical scavenging to clean NO so that pulp healing can occur better by increasing the number of fibroblast cells that play a role in wound healing. Purpose: To determine the concentration of hydrogel EGCGs that are effective in increasing the number of fibroblast cell proliferation in the dental pulp perforation of Wistar rats. Method: This research is a laboratory experimental study with a randomized post test only control group design. Samples used in the study were 24 male Wistar rats which were divided into four groups, namely the negative control group and the treatment group were given EGCG 60 ppm, 90 ppm, and 120 ppm and were decapitated on the 7th day after treatment. The maxilla and the 1st molar were taken and decalcified, to process the HPA reading with HE staining. Observations were made using a microscope with a magnification of 400x. Results: There were significant differences in the treatment groups with 60 ppm and 90 ppm hydrogel hydrogels on the results of the Oneway ANOVA difference test (p <0.05). Conclusion: The concentration of hydrogel EGCG which is effective in increasing fibroblast cell proliferation is 90 ppm.